Case studies of construction entrepreneurship in Singapore - Wong, Yue Rui. (2009)
Case studies of construction entrepreneurship in Singapore is a dual project aim to provide a study of the success stories behind enterprising contractor and consultant firms, specifically looking into the characteristics these entrepreneurs.